A NON-INVASIVE METHODS FOR DIAGNOSING AND SEGREGATION OF ELECTRICAL AND BEARING FAULTS IN INDUCTION MOTORS - SHEIKH, MUHAMMAD AMAN (2018)
Online condition monitoring of an induction motor is very important to potentially increase the reliability of motor which ultimately reduce down-time and manpower. In induction motor stator winding and bearing accounts 37 % and 41 % of failures. In bearing these faults are caused by contamination and lubrication issues while the stator faults are caused by insulation breakdown.